Factors to improve quality for older patients in the emergency department: a qualitative study of patient trajectory - Isabelle De Brauwer; Pascale Cornette; William D'Hoore; Vincent Lorant; Franck Verschuren; Frédéric Thys; Isabelle Aujoulat (BMC, 2021)
Abstract Background Managing older people in the emergency department remains a challenge. We aimed to identify the factors influencing the care quality of older patients in the emergency department, to fine-tune future interventions for older people, considering the naturalistic context of the ED. Methods This is a qualitative study of some 450 h of observations performed in three emergency departments selected for their diverse contexts. We performed seventy observations of older patient trajectories admitted to the emergency department. Themes were extracted from the material using an inductive reasoning approach, to highlight factors positively or negatively influencing management of patient's trajectories, in particular those presenting with typically geriatric syndromes. Results Four themes were developed: no geriatric flow routine; risk of discontinuity of care; unmet basic needs and patient-centered care; complex older patients are unwelcome in EDs. Conclusions The overall process of care was based on an organ- and flow-centered paradigm, which ignored older people's specific needs and exposed them to discontinuity of care. Their basic needs were neglected and, when their management slowed the emergency department flow, older people were perceived as unwelcome. Findings of our study can inform the development of interventions about the influence of context and organizational factors.